Pola kelarutan miosin dan kapasitas emulsinya pada berbagai suhu=Solubility Pattern of Myosin and It's Emulsifying Capacity at Various Tempereture - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Many factors affect meat emulsion stability, among this, is the optimum condition of emulsifier used. Myosin as a component of meat protein, can be utilized as an emulsifier. However, the optimum condition of myosin as meat emulsifier in not known. In this study, beef myosin was extracted with 0,6 M KC1